1997
DOI: 10.1046/j.1365-2265.1997.2791084.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in Turner's syndrome—a longitudinal study

Abstract: As there is little evidence of reduced bone mineral density in girls with Turner's syndrome there is no justification for an early introduction of oestrogen replacement during the prepubertal years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 15 publications
5
31
1
1
Order By: Relevance
“…Previous studies showed that GH-and HRT-treated patients had normal lumbar BMD by DXA, suggesting that the axial trabecular bone was preserved in young adults with TS. 9,13,15 On the other hand, skeletal sites with predominantly cortical bone had a reduced BMD measured by DXA, pQCT and QUS. [9][10][11][12]38,39 Recently, Hansen and colleagues, using high-resolution pQCT, observed that adult TS women (mean age 35 years, range 20-61) also had defective trabecular micro-architecture at the distal radius and tibia compared to healthy adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that GH-and HRT-treated patients had normal lumbar BMD by DXA, suggesting that the axial trabecular bone was preserved in young adults with TS. 9,13,15 On the other hand, skeletal sites with predominantly cortical bone had a reduced BMD measured by DXA, pQCT and QUS. [9][10][11][12]38,39 Recently, Hansen and colleagues, using high-resolution pQCT, observed that adult TS women (mean age 35 years, range 20-61) also had defective trabecular micro-architecture at the distal radius and tibia compared to healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Conversely, it was observed that TS patients receiving appropriate oestrogen treatment usually showed normal trabecular BMD after adjusting for body size. [13][14][15][16][17] In addition to Hormonal Replacement Therapy (HRT), Growth Hormone (GH) administration is considered standard treatment for TS girls, but the role of GH in promoting bone accrual has not yet been completely defined. [18][19][20] Several studies reported in TS patients an increase in fracture prevalence and risk that was higher during childhood and after the age of 45.…”
mentioning
confidence: 99%
“…(7,8) Similarly, when TS patients were compared to individuals with the same age and height, bone mass appeared ample for bone size. (15,16) Thus other aspects of bone characteristics such as bone geometry (17) or cortical and/or trabecular microarchitecture may be altered in TS, possibly compromising skeletal integrity and increasing the risk of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Female patients with Turner’s syndrome usually present with smaller bone and body sizes in comparison with normal women [1]. Because areal BMD (aBMD), usually assessed by current densitometric techniques, is influenced by bone dimensions and height [8, 9, 10], the reduced bone and body sizes might determine an ‘apparent’ low aBMD in these patients [1, 2, 11]. To elucidate this issue, we measured the volumetric BMD (vBMD), which is less dependent on body and bone sizes [9], in young women with Turner’s syndrome on estrogen replacement therapy (ERT) from adolescence.…”
Section: Introductionmentioning
confidence: 99%